Restricted loss of olivocochlear but not vestibular efferent neurons in the senescent gerbil (Meriones unguiculatus) - Radtke-Schuller, Susanne; Seeler, Sabine; Grothe, Benedikt (Frontiers in Aging Neuroscience, 2015)
Degeneration of hearing and vertigo are symptoms of age-related auditory and vestibular disorders reflecting multifactorial changes in the peripheral and central nervous system whose interplay remains largely unknown. Originating bilaterally in the brain stem, vestibular and auditory efferent cholinergic projections exert feedback control on the peripheral sensory organs, and modulate sensory processing. We studied age-related changes in the auditory and vestibular efferent systems by evaluating number of cholinergic efferent neurons in young adult and aged gerbils, and in cholinergic trigeminal neurons serving as a control for efferents not related to the inner ear. We observed a significant loss of olivocochlear (OC) neurons in aged compared to young adult animals, whereas the overall number of lateral superior olive (LSO) cells was not reduced in aging. Although the loss of lateral and medial olivocochlear (MOC) neurons was uniform and equal on both sides of the brain, there were frequency-related differences within the lateral olivocochlear (LOC) neurons, where the decline was larger in the medial limb of the superior olivary nucleus (high frequency representation) than in the lateral limb (middle-to-low frequency representation). In contrast, neither the number of vestibular efferent neurons, nor the population of motor trigeminal neurons were significantly reduced in the aged animals. These observations suggest differential effects of aging on the respective cholinergic efferent brainstem systems.